The Oxford history of music vol. I: the polyphonic period. Part I: method of musical art, 330-1330 - Woolridge, H. E. (Oxford Clarendon Press, 1901)
Excerpt from The Oxford History of Music, Vol. 1: The Polyphonic Period; Part I; Method of Musical Art, 330-1330IN considering the development Of the resources of pure sound, regarded as a material for artistic treatment, the phenomena may be seen as arranging themselves in three main divisions or periods, each representing a totally distinct phase Of artistic activity in relation to the material and a different view of its capabilities.The first period represents that phase in which the beauty to be Obtained from the material is perceived only as consisting in certain arrangements Of consecutive simple sounds; the aim Of the artist is Single, and its outcome is the coherent individual utterance, or Melody. This was the music of the Old Greeks and is still the music of all eastern people.